Compliance analysis of sentence structure helps maintain consistency throughout the text. Consistent sentence structures contribute to the overall coherence of the writing, enhancing the reader's understanding and engagement with the content. - Adi Setyawan; Desi Ratna (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to evaluate the impact of creative dance using various learning methods on the progress of gross motor skills in children. The experimental group took part in a creative dance program with various learning methods, while the control group experienced no special intervention. Gross motor skills were measured before and after the intervention using standard tests. These results show that a creative approach to dance, supported by a variety of learning methods, can effectively improve the progress of gross motor skills in preschool children. This research makes a positive contribution to our understanding of the importance of integrating creative dance and diverse learning methods in the development of children's gross motor skills